THE ROLE OF INFORMATION TECHNOLOGY IN IMPROVEMENT OF QUALITY OF THE FINANCIAL REPORTS PREPARED BY THE COMMERCIAL BANKS IN BANGLADESH - Sina, Md. Abu; Chowdhury, Md. Shahnur Azad; Shakib, Md. Tafhim; Akter, Sultana; Arafat, A. B. M. Yasir (Indian Journal of Finance and Banking, 2021)
In the 21st century, from bank to insurance, multinational companies to government offices have increased thousands of times their profitability, productivity, sustainability, and also market expansion through the successful uses of ICT. Today another aspect is the preparation of a high-quality financial report that relies entirely on the information. Quality information depends on several characteristics like completeness, accuracy, timeliness, consistency, validity, accessibility, and integrity of that information, etc. Having these characteristics in financial information is the prerequisite for good financial reporting. Usages of IT have a great role in producing quality information and financial reporting consequently. The use of IT in the banking sector is more sophisticated than in other sectors in Bangladesh. Therefore, the purpose of this research is to examine analytically the relationship between the use of Information Technology and the quality of financial reporting. Using primary data sourced a structured questionnaire was administered to selected banks in Bangladesh and data analysis was done through the General Regression Model by OLS method to examine the nature of the relationship that exists between the quality of financial reports and the Adoption of Information Technology. The result of the data analysis of the study showed that a positive correlation exists between IT and the quality of reports. JEL Classification Codes: M1, M15, Q55.